1988
DOI: 10.2134/agronj1988.00021962008000050029x
|View full text |Cite
|
Sign up to set email alerts
|

Spring Wheat and Barley Responses to Ethephon

Abstract: Ethephon [(2‐chloroethyl) phosphonic acid] has recently been introduced in North America as a regulator to control lodging in cereals. A 3‐yr study (1983‐1985) was conducted to determine how widely grown spring wheat (Triticum aestivum L.) and spring barley (Hordeum vulgare L.) cultivars in the North Central United States responded to ethephon. Nine randomized complete‐block, split‐plot experiments with wheat, and seven with barley, were conducted at the Crookston (soil classification, Aeric Calciaquoll), Morr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
75
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(94 citation statements)
references
References 7 publications
18
75
1
Order By: Relevance
“…Furthermore, the decrease in grains spike-I and grain mass with PGR application may be the result of the increased number of tillers (intra-plant competition). The yield reductions with ethephon applications are in keeping with the results of Simmons et al (1988), Moes and Stobbe (1991) and Rowland (1973), who reported yield reductions after ethephon application. In the current study it was found that yield reductions were evident when the flag leaf and split applications were employed (Figures 4a, b).…”
Section: Plant Height and Lodgingsupporting
confidence: 88%
See 2 more Smart Citations
“…Furthermore, the decrease in grains spike-I and grain mass with PGR application may be the result of the increased number of tillers (intra-plant competition). The yield reductions with ethephon applications are in keeping with the results of Simmons et al (1988), Moes and Stobbe (1991) and Rowland (1973), who reported yield reductions after ethephon application. In the current study it was found that yield reductions were evident when the flag leaf and split applications were employed (Figures 4a, b).…”
Section: Plant Height and Lodgingsupporting
confidence: 88%
“…Simmons et al (1988) reported a 10.5% increase in grain yield averaged over three barley cultivars after treatment with ethephon at the flag leaf stage. Moes and Stobbe (1991) found significant improvements in all three yield components after ethephon treatment in the first year of a study.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Amongst PGRs Ethephon (2-chloroethyl phosphonic acid) (ET) and Chlormequat chloride (CCC) have been effective in decreasing plant height and reducing lodging incidence in wheat (Crook and Ennos 1995). However, the effectiveness of PGRs in controlling lodging depends on many factors including variety, type of growth regulator, its application rate (Bahry, 1988), crop growth stages at the time of application (Caldwell et al, 1988) and its dose (Simmons et al, 1988). There was no published information on the effects of timing, type and dose of PGRs on lodging and yield of Bere.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recent investigations on the use of Ethrel in finger millet [7] resulted in the production of some hybrids. Other benefits to using Ethrel include the reduction in plant height, which leads to reduced lodging, and increased grain yield [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%